Design and Cost Estimation of a Gas-Filled Membrane Absorption (Gfma) Process as Alternative for Cyanide Recovery in Gold Mining - Romero-Figueroa, J; Estay-Cuenca, H (Elsevier, 2014)
Cyanide recovery processes are currently an attractive technology implemented in gold mining. The reduction of operational costs, along with minimization or avoidance of the use of expensive processes in destroying cyanide, are among the main reasons that might persuade the gold mining industry to adopt these technologies. The SART and AVR processes are the most frequently implemented in the past years, although both technologies have high requirements of footprint area, equipment sizes and reagents consumption. The present work proposes a novel cyanide recovery technology based on membrane absorption to recover cyanide in gold mining. This study reports the design and cost estimation for cyanide recovery by means of the gas-filled membrane absorption (GFMA) process, which was previously characterized by experimental trials using a commercial hollow fiber contactor, and the modeling of its mass transfer was also carried out. Furthermore, preliminary economic studies of the GFMA, AVR and SART processes were done in order to evaluate the feasibility of the GFMA process. Results from this work suggest that the membrane absorption process could reduce the requirements of footprint area and energy consumption, yielding a net present value at least 35% higher than the AVR process and competitive with the SART process. Hence, the membrane absorption process here proposed is a viable and attractive alternative to current cyanide recovery processes, especially under specific operation conditions, such as low copper concentration in solutions or limitations in flow configuration, where the implementation of the SART process becomes difficult. © 2014 Elsevier B.V.